Effect of Azospirillum brasilense on yield components of maize - Segismundo, Vinícius Duarte [UNESP]; De Oliveira, Kevyn Belonssi [UNESP]; Silva, Jussara Barros [UNESP]; Santos, Lucélia De Fátima [UNESP]; Môro, Gustavo Vitti [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
Among the countless operations involved in the maize production system, nitrogen fertilization is essential for the crop yield and development. However, due to the costs and negative environmental impacts caused by chemical fertilization, the use of the bacterium Azospirillum brasilense is an alternative to reduce costs and increase yield. Thus, this study evaluates the effect of inoculation of Azospirillum brasilense on the yield components of synthetic varieties of maize. The experiments were carried out at UNESP - Jaboticabal Campus, state of São Paulo, Brazil. The randomized block design was used with two replicates, testing fortysix maize genotypes: forty-four synthetic genotypes and two checks. Experiments were performed without nitrogen topdressing and with Azospirillum brasilense inoculation and, with nitrogen topdressing and without Azospirillum brasilense inoculation. Grain yield, average weight of grains, prolificacy, ear length, ear diameter, number of rows and number of grains per row were evaluated. The analysis of combined variance of experiments was performed considering the effects of genotypes, experiments, and the Genotype x Experiment interaction. Using the means from the analysis of variance, the Scott-Knott test was applied at 5% probability for the cases in which the F test was significant. It was found that bacterial inoculation increased yield, average weight of grains, ear diameter, and number of rows, while nitrogen fertilization increased prolificacy, ear length, and number of grains per row.
Efeito do Azospirillum brasilense nos componentes da produção do milho
Keywords: Biological N fixation; Diazotrophic bacteria; Nitrogen fertilization; Zea mays